Innovation of secondary packaging “nasi ayam” / Muhammad Saifuddin Muhammad Zainuddin ... [et al.] - Muhammad Zainuddin, Muhammad Saifuddin; Omar, Mastura; Mohd Rosnan, Shalida; Abdul Rahman, Andrialis; Mohd Muslim Tan, Ellyana (Universiti Teknologi MARA, Kedah, 2023)
Secondary packaging functions as outer packaging to keep the product safer and organized. This is because it makes it easier for customers to carry and if it falls, the product is still safe. In addition, it also serves as a useful shipping container in e-commerce. Secondary packaging also has many components such as boxes, padding, separators, reinforcements, bags, and others. Therefore, I have chosen to make secondary packaging for chicken rice. I have created a packaging mockup that is more effective to use. I have made the rice no need to use plastic to carry it, in fact, I have made a handle for the packaging. In addition, I have placed an AR scanner and QR code. QR Code works directly to directions to the place of business. The objective I created for Secondary Packaging is to make it easier for customers to carry the purchased chicken rice. This is because it can attract customers to buy chicken rice. In addition, secondary packaging can strengthen the selected product. This is because secondary packaging needs to be custom-made. Plastic packaging is not suitable for carrying food like chicken rice because it can cause environmental pollution. The innovation from my packaging is to have a place to put the sauce and soy sauce in the package. In addition, I have provided a place for the handle to be easily carried by the customer. It is also combined with Augmented Reality (AR) and Quick Response (QR). In conclusion, secondary packaging is very important to use. This is because it makes the product neater and stronger. With that, the secondary packaging I made can reduce the use of plastic in packaging and it is safe to use in nutritional products such as Chicken Rice.